The Effect of Muscle Energy Technique and Posture Correction Exercises on Pain and Function in Patients with Non-specific Chronic Neck Pain Having Forward Head Posture—a Randomized Controlled Trail - Joshi, MPT, Reema; Poojary, BPT, Nishita (International journal of therapeutic massage & bodywork, 2022)
Background: Neck pain is a common problem in individuals despite different types of working patterns. Forward head posture is a common identified cause of chronic neck pain in patients. The effect of long-term forward head posture can be loss of function which can limit individuals’ capacity to work or do activities of daily living; hence it becomes necessary to intervene with muscle strengthening to improve neck stability, as well as mobility.Purpose: To assess effectiveness of muscle energy technique (MET) and posture correction exercises on pain and function in patients with non-specific chronic neck pain having forward head posture.Study Setting: Outpatient department of Dr. D. Y. Patil College of Physiotherapy, Pune, India.Participants: Both males and females between the ages of 21-60 years with a cranio-vertebral angle of less than 48° were included in study.Research Design: A randomized clinical trial. Methodology: MET group received muscle energy treatment + posture correction exercises, and control group receiving neck range of motion treatment. Outcomes measures were pain (Numerical Pain Rating Scale), function (Neck Disability Index), and cranio- vertebral angle (MB ruler).Results: Forty-eight subjects were included in the analysis, with 23 participants in Group A (MET) and 25 in Group B (Control). While both groups showed within-group improvements, Group A had significantly greater decreases in neck pain (p < .001), Neck Disability Index scores (p < .001), and significantly greater improvements in cranio-vertebral angles (p < .025) compared to group B.Conclusion: The combined effect of MET and posture correction exercises provides significantly greater results than neck range of motion treatment, and muscle energy technique should be included in the treatment of non-specific chronic neck pain in individuals with forward head posture.